2(z-4)+3z=4-(z+2)

Simple and best practice solution for 2(z-4)+3z=4-(z+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(z-4)+3z=4-(z+2) equation:


Simplifying
2(z + -4) + 3z = 4 + -1(z + 2)

Reorder the terms:
2(-4 + z) + 3z = 4 + -1(z + 2)
(-4 * 2 + z * 2) + 3z = 4 + -1(z + 2)
(-8 + 2z) + 3z = 4 + -1(z + 2)

Combine like terms: 2z + 3z = 5z
-8 + 5z = 4 + -1(z + 2)

Reorder the terms:
-8 + 5z = 4 + -1(2 + z)
-8 + 5z = 4 + (2 * -1 + z * -1)
-8 + 5z = 4 + (-2 + -1z)

Combine like terms: 4 + -2 = 2
-8 + 5z = 2 + -1z

Solving
-8 + 5z = 2 + -1z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add 'z' to each side of the equation.
-8 + 5z + z = 2 + -1z + z

Combine like terms: 5z + z = 6z
-8 + 6z = 2 + -1z + z

Combine like terms: -1z + z = 0
-8 + 6z = 2 + 0
-8 + 6z = 2

Add '8' to each side of the equation.
-8 + 8 + 6z = 2 + 8

Combine like terms: -8 + 8 = 0
0 + 6z = 2 + 8
6z = 2 + 8

Combine like terms: 2 + 8 = 10
6z = 10

Divide each side by '6'.
z = 1.666666667

Simplifying
z = 1.666666667

See similar equations:

| -7v+5v=-2-8 | | 11x=60.5 | | 4-3x=8x+14 | | 7y-10-5y+5=0 | | z-5z=-4 | | -(5x+2)=8 | | -2x+15=-17 | | 4u=-7 | | 44*.5= | | 3x^2-23x+13=0 | | -(11x^2+2x-1)= | | -6+5x=2+3x-2x | | 14v-16v=40 | | (1/5)x=-14 | | X/x+2=5/4 | | 77=4x+7x | | 4t^2+28t=0 | | 81-y^2=0 | | 16x-6=36x+9 | | x-(1/10)=(1/9) | | -2x-8=-6x-52 | | -7(x+2)-12=25+5 | | 2x/x^2-25=10/x^2-25-3/x+5 | | 16=8w-4/2 | | -10+5=x+8 | | 36b^2-49t^2= | | S=uz | | 7x^2-10x+10=0 | | 17-5+x=5+8-1 | | 96-y=3y | | 12a^2-11a-15= | | X-9/4-3=x-7/3 |

Equations solver categories